(untitled) (Research, Society and Development, 2023)
Descriptive study with a qualitative approach, with 27 companions of children admitted to a pediatric hospital in Rio de Janeiro. The objective was to characterize the companions of the child hospitalized in the inpatient unit awaiting an elective surgical procedure and describing their vision of safe surgery. To collect the collected data, a semi-structured interview was carried out. Data were formed from the content analysis proposed by Bardin. From the analysis, two categories emerged: Ignorance on the subject and Safe Surgery: a set of concepts. We realized that the Safe Surgery theme, as well as other international safety goals, are not widespread among study participants. It is necessary to propose and implement strategies that promote spaces for discussion and shared construction of knowledge, with a set of including the patient in patient safety issues.